Psychology Beyond the Discipline: A Critical Analysis of Interdisciplinary Integration, Regulatory Frameworks, and Pedagogical Efficacy in Indian Higher Education (2020 - 2025) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Indian higher education landscape is undergoing a profound transformation following the National Education Policy (NEP) 2020, which mandates a shift from rigid disciplinary silos toward multidisciplinary learning ecosystems. Psychology, traditionally confined to social science departments, is now being reimagined as a foundational “hub science” essential across diverse undergraduate programs. This comprehensive review examines the integration of psychology in engineering, business, healthcare, law, and teacher education between 2020 and 2025, analysing over 700 research inputs including government reports, university syllabi, and empirical studies. The analysis reveals that while interdisciplinary psychology education significantly enhances critical thinking, emotional intelligence, and professional competencies, implementation faces substantial challenges from regulatory conflicts - particularly the National Commission for Allied and Healthcare Professions (NCAHP) Act 2021 and the 2024 University Grants Commission (UGC) ban on distance education psychology degrees. This paper argues for distinguishing “clinical psychology” (healthcare profession) from “applied psychology” (academic discipline) to resolve regulatory tensions while advocating for systematic integration of psychological literacy across curricula, including indigenous Indian Knowledge Systems (IKS). The findings demonstrate that psychology integration is not merely academically relevant but structurally necessary for preparing graduates to navigate the complex interface of human behaviour and technical systems in contemporary society.